Pathogenic effects and prepatent periods of Trypanosoma evansi isolates from Indonesia in mice - Sawitri, Dyah H.; Wardhana, April H.; Sadikin, Mohamad; Wibowo, Heri; Desquesnes, Marc (Universiti Kebangsaan Malaysia, 2022)
Trypanosoma evansi is an extracellular blood protozoan parasite that causes Surra in livestock, but only a few studies have been conducted on the pathogenicity of its isolates. Meanwhile, it was discovered that the rate of parasite growth and the length of the prepatent periods were equivalent in different strains of cattle and mice. Thus, further research into the pathogenic effects and pre-patent periods of T. evansi in mice is necessary to aid in the epidemiological understanding and field treatment strategy for Surra. The purpose of this study was to ascertain the pathogenic potential of T. evansi isolates from Indonesia and their prepatent periods. A total of 32 T. evansi isolates from various regions in Indonesia were inoculated intraperitoneally into three male DDY mice (104 parasites/0.3 mL) for each isolate. Additionally, the parasitaemia level and mortality of the mice were determined every 2 days, and the data were analysed using ANOVA with a 95% confidence level. The results indicated that T. evansi isolates exhibited virulence levels classified as high, moderate and low. Each virulence exhibited a distinct parasitaemia pattern. However, high virulence was not associated with short prepatent periods. The results indicated that the surra epidemic in Indonesia is characterised by strains with varying degree of virulence in water buffaloes necessitating the development of effective treatment strategies.